2012
DOI: 10.1177/0146167212455828
|View full text |Cite
|
Sign up to set email alerts
|

How Much Information? East Asian and North American Cultural Products and Information Search Performance

Abstract: Literature in cultural psychology suggests that compared with North Americans, East Asians prefer context-rich cultural products (e.g., paintings and photographs). The present article further examines the preferred amount of information in cultural products produced by East Asians and North Americans (Study 1: Society for Personality and Social Psychology conference posters; Study 2: government and university portal pages). The authors found that East Asians produced more information-rich products than did Nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 36 publications
1
60
0
Order By: Relevance
“…Although positive mood participants did not quite perform worse than negative mood participants on a single task, positive people tended to perceive the single task to be more difficult than did people in a negative mood (the reverse is true for the three-task condition). While it might be that processing style makes it easier to perceptually process more things at once-trait holistic processors have been found to prefer more complex and information-rich visual products, such as art, graphic design, and websites (Wang et al 2012) and draw pictures with more background and details (Masuda et al 2008)-this also leaves open the possibility that only processing one thing, with little other context or complexity, may be more difficult to do while processing holistically.…”
Section: Study 2 Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although positive mood participants did not quite perform worse than negative mood participants on a single task, positive people tended to perceive the single task to be more difficult than did people in a negative mood (the reverse is true for the three-task condition). While it might be that processing style makes it easier to perceptually process more things at once-trait holistic processors have been found to prefer more complex and information-rich visual products, such as art, graphic design, and websites (Wang et al 2012) and draw pictures with more background and details (Masuda et al 2008)-this also leaves open the possibility that only processing one thing, with little other context or complexity, may be more difficult to do while processing holistically.…”
Section: Study 2 Discussionmentioning
confidence: 99%
“…This was potentially due to preference for more visual and information rich environments by holistic processors. A follow-up study revealed that holistic processors were able to find a target image in a visually "busy" web page more quickly than were analytic processors (Wang et al 2012). Holistic processing style (indicated by cultural background) also predicts preference for attending to global configurations rather than prioritizing the individual local elements in a figure (McKone et al 2010).…”
Section: Audience-level Processing Styles: Analytic and Holistic Procmentioning
confidence: 97%
See 3 more Smart Citations